2011
DOI: 10.1007/s00415-011-6172-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vertical and horizontal saccade measures and their relation to gray matter changes in premanifest and manifest Huntington disease

Abstract: Saccades are a potentially important biomarker of Huntington disease (HD) progression, as saccadic abnormalities can be detected both cross-sectionally and longitudinally. Although vertical saccadic impairment was reported decades ago, recent studies have focused on horizontal saccades. This study investigated antisaccade (AS) and memory guided saccade (MG) impairment in both the horizontal and vertical directions in individuals with the disease-causing CAG expansion (CAG+; n = 74), using those without the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…We further found consistent atrophy in the inferior parietal cortex and intraparietal sulcus, playing an important role in higher cognitive functioning and somatosensory and visuomotor integration [50]. For instance, Rupp et al [51] reported significant associations between degeneration in the left inferior parietal lobule and antisaccade in HD, an important phenotypical feature in HD. Finally, volume reductions in the insula were associated with emotion processing deficits in HD, especially for the recognition of disgust, which is already detectable before symptom onset [52].…”
Section: Discussionsupporting
confidence: 55%
“…We further found consistent atrophy in the inferior parietal cortex and intraparietal sulcus, playing an important role in higher cognitive functioning and somatosensory and visuomotor integration [50]. For instance, Rupp et al [51] reported significant associations between degeneration in the left inferior parietal lobule and antisaccade in HD, an important phenotypical feature in HD. Finally, volume reductions in the insula were associated with emotion processing deficits in HD, especially for the recognition of disgust, which is already detectable before symptom onset [52].…”
Section: Discussionsupporting
confidence: 55%
“…For example, quantitative measurements of eye movements such as saccade latency and duration, as well as errors in oculomotor tasks, have been studied as possible biomarkers of presymptomatic and early symptomatic stages of HD (Ali, Michell, Barker, & Carpenter, 2006;Blekher et al, 2006;Golding, Danchaivijitr, Hodgson, Tabrizi, & Kennard, 2006;Patel, Jankovic, Hood, Jeter, & Sereno, 2012). The results from clinical HD patients have consistently shown significantly increased saccadic latencies (Ali et al, 2006;Antoniades, Xu, Mason, Carpenter, & Barker, 2010;Avanzini, Girotti, Caraceni, & Spreafico, 1979;Blekher et al, 2006;Golding et al, 2006;Patel et al, 2012;Rupp et al, 2012), saccadic durations (Ali et al, 2006;Avanzini et al, 1979), and errors in saccadic direction (Blekher et al, 2006;Patel et al, 2012;Rupp et al, 2012). Also, increased saccadic latencies (Blekher et al, 2006;Golding et al, 2006;Robert et al, 2009) and errors in saccadic direction have been reported in presymptomatic stages (Blekher et al, 2006).…”
mentioning
confidence: 82%
“…Motor impairment, including psychomotor performance, is associated with striatal volume (and other basal ganglia) loss in HD patients (Jurgens et al, 2008;Ruocco, Bonilha, Li, Lopes-Cendes, & Cendes, 2008;Scahill et al, 2013;Van Den Bogaard et al, 2011) and premanifest gene carriers (Biglan et al, 2009;Vandenberghe et al, 2009) and extends to cortical areas for psychomotor and visual motor tasks (Bechtel et al, 2010;Jurgens et al, 2008;Rupp et al, 2012;Scahill et al, 2013). Poor performance during emotion recognition, executive function, memory, and olfactory tasks is also associated with a reduced volume in both the striatum (Henley et al, 2012) and cortex (Henley et al, 2012;Ille et al, 2011;Papp et al, 2013;Scahill et al, 2013).…”
Section: Structural Imagingmentioning
confidence: 99%